2021
DOI: 10.55563/clinexprheumatol/6oq9du
|View full text |Cite
|
Sign up to set email alerts
|

Possible implication of intermolecular epitope spreading in the production of anti-glomerular basement membrane antibody in anti-neutrophil cytoplasmic antibody-associated vasculitis

Abstract: ObjectiveAnti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is sometimes complicated by anti-glomerular basement membrane (GBM) disease. Proteases, including elastase, released from neutrophils activated by ANCA are implicated in the pathogenesis of AAV. Epitopes of anti-GBM antibody exist in the α3-subunit non-collagenous (NC1) domain of collagen type IV [Col (IV)]. This region, called α3(IV)NC1, is structurally cryptic. This study aimed to determine the production mechanism of anti-GBM a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…One recent study suggests that proteases released by neutrophils activated by ANCA digest collagen type IV to expose GBM epitopes. 25 Following this, CD11c+ macrophages specific to ANCA-associated vasculitis are responsible for antigen presentation of the GBM epitopes to T cells, resulting in the production of anti-GBM antibodies. Moreover, in an in vitro study using human cells, Kubala et al 26 demonstrated that MPO binds to collagen IV in the extracellular matrix in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study suggests that proteases released by neutrophils activated by ANCA digest collagen type IV to expose GBM epitopes. 25 Following this, CD11c+ macrophages specific to ANCA-associated vasculitis are responsible for antigen presentation of the GBM epitopes to T cells, resulting in the production of anti-GBM antibodies. Moreover, in an in vitro study using human cells, Kubala et al 26 demonstrated that MPO binds to collagen IV in the extracellular matrix in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…5 cases showed granular deposition of IgG1 along the mesangial area and capillary wall, and the other case was negative. The latest study showed that the release of ANCA can damage the kidney and then result in the revelation of a3(IV)NC1, leading to in ltration of CD11c + macrophages, subsequently the exposed GBM epitope can induce the formation of anti-GBM antibodies [12] . Furthermore, there are data showing that the target antigen of anti-GBM in anti-GBM positive patients is the NC1 region of the α3 chain of type IV collagen, irrespective of whether they are combined with ANCA or not [13] .…”
Section: Anti-gbm + Ancamentioning
confidence: 99%
“…The pathogenic mechanism of this association is still debated, but since low levels of ANCA may be detected years before the appearance of anti-GBM antibodies and clinical symptoms, it has been hypothesised that ANCA antibodies may induce glomerular inflammation that modify or expose usually sequestered disease epitopes in GBM, triggering anti-GBM antibodies formation (28). A recent study by Nishibata demonstrated that proteases released from neutrophils activated by ANCA can digest type IV collagen with subsequent unveiling of alpha-3(IV) NC (60). Another study demonstrated that up to 60% anti-GBM patients also have autoantibodies that target linear epitopes of MPO, versus 24% with autoantibodies that target intact MPO.…”
Section: Other Variantsmentioning
confidence: 99%